Who Goes Where and Why: An Overview and Analysis of Global Educational Mobility - Bista, Krishna (Journal of International Students, 2012)
The number of international students and scholars studying and working in a culture beyond their own has significantly increased in past few years. The mobility of students and scholars bring a diverse and global educational exchange of cultures, ideas, and technological innovations to the culture of colleges and universities. In this context, Who Goes Where and Why, written by Caroline Macready and Clive Tucker (2011), is a significant contribution to the field of international student mobility and study abroad. In this book, the authors analyze the trends of students on why and how they study overseas, and how the national policies of hosting and sending countries affect the decisions of those mobile students.